Aplikasi Image Enhancement untuk Peningkatan Kualitas Citra Ultrasonografi Ginjal - Ni Larasati Kartika Sari; Inti Ermina Br Barus; Budi Santoso; Dewi Muliyati; Purwantiningsih Purwantiningsih; Idris Kusuma (Jurnal Ilmiah Giga, 2022)
Abstract. Combination of four filters namely gaussian filter, median filter, wiener filter, average filter were tested using two contrast enhancement techniques, intensity adjustment and histogram equalization, were tested to improve the quality of kidney ultrasound images. The research was conducted using 40 images, consist of 9 normal images, 17 hydronerfosis images, and 14 kidney stones images. The measured image quality were PSNR (Peak Signal to Noise Ratio) and MSE (Mean Square Error). The higher the PSNR and the lower the MSE, the better the image quality. Visual evaluation through questionnaires to clinicians has also been carried out to assess the visualization of the kidney and its abnormalities. The results of PSNR and MSE calculations showed that every image processings methods combinations produce different results in each image categories. However, whether in normal, hydronefrosis, or kindey stone categories, the combination of filters with image adjustment method gave the highest PSNR and lowest MSE. Meanwhile, the results of the visual evaluation from the clinicians showed that the best image enhancement technique in improving the visualization of abnormalities in kidney ultrasound images (Hydronephrosis and kidney stones) was the combination of a wiener filter with intensity adjustment, in accordance with the results of the PSNR measurement.Abstrak.  Telah diuji kombinasi empat metode filter yaitu gaussian filter, median filter, wiener filter dan average filter dengan peningkatan kontras, intensity adjustment dan histogram equalization untuk meningkatkan kualitas citra ultrasonografi ginjal. Penelitian dilakukan dengan menggunakan 40 citra, dengan rincian 9 citra normal, 17 citra Hydronerfosis, dan 14 citra batu ginjal. Kualitas citra yang diukur adalah PSNR dan MSE. Evaluasi visual melalui kuesioner terhadap klinisi juga telah dilakukan. Untuk citra normal, nilai PSNR tertinggi, yaitu 14.21 dan MSE  terendah, yaitu 2.62 diperoleh pada kombinasi median filter dengan intensity adjustment. Untuk citra hydronefrosis, PSNR tertinggi diperoleh pada kombinasi wiener filter dengan intensity adjustment, yaitu 4.42 dan nilai MSE terendah diperoleh pada kombinasi average filter dengan intensity adjustment, yaitu 3.37. Pada citra batu ginjal, nilai PSNR tertinggi diperoleh pada kombinasi wiener filter dengan intensity adjustment, yaitu 15.48, serta nilai MSE terendah merupakan kombinasi gaussian filter dengan intensity adjustment, yaitu 3.23. Sementara itu, hasil evaluasi visual dari dokter klinisi menunjukkan bahwa teknik image enhancement yang paling baik dalam meningkatkan visualisasi abnormalitas pada citra USG ginjal hydronefrosis dan batu ginjal adalah merupakan kombinasi wiener filter dengan  intensity adjustment, sesuai dengan hasil pengukuran PSNR.